ARAYA V. NEVSUN RESOURCES: REMEDIES FOR VICTIMS OF HUMAN RIGHTS VIOLATIONS COMMITTED BY CANADIAN MINING COMPANIES ABROAD - Lauzon, Jolane (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2018)
In November 2017, the British Columbia Court of Appeal (BCCA) published its decision in the case Araya v. Nevsun Resources, dismissing the appeal filed by Nevsun, and allowing the lawsuit to move forward to the merits stage of the procedure. This decision was ground-breaking since the plaintiffs were suing Nevsun Resources, a Canadian mining company, for its alleged complicity in the use of forced labor, slavery, torture, inhuman or degrading treatment, and crimes against humanity at the Bisha Mine in Eritrea, a mine belonging to Nevsun. In its decision, the BCCA rejected the three main arguments put forward by Nevsun to get the case dismissed: (1) the forum non conveniens doctrine; (2) the Act of State doctrine and (3) the lack of private law cause of action against corporations for the violations of customary international law principles. In this context, this article offers an analysis of the most significant cases brought before Canadian Courts in regard to Canadian mining companies’ corporate social responsibility. It also relies on two influential cases from the U.S. Supreme Court: Kiobel v. Royal Dutch Petroleum and Jesner v. Arab Bank. Finally, it looks at the common challenges faced by foreign victims when they seek to bring lawsuits against transnational corporations and it briefly suggests that common law courts should adopt a new duty of care to address businesses’ corporate liability for violations of human rights.